2013
DOI: 10.1139/cjb-2013-0014
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal patterns of nitrogen fixation in biological soil crusts from British Columbia’s Chilcotin grasslands

Abstract: This study provides estimates of N2 fixation in biological soil crusts (BSCs) from shrub–steppe grasslands in British Columbia’s Chilcotin plateau. We identify key seasonal periods and environmental conditions during episodes of BSC nitrogen-fixation activity. Predicted nitrogen-fixation activity showed two peak periods: one during late winter and early spring snowmelt events, and the second during summer precipitation events. BSC nitrogen fixation, especially summer activity, was quite variable from year to y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
0
17
0
2
Order By: Relevance
“…14.3). Barger (2003), Barger et al (2013), Belnap (2002a, b), Billings et al (2003), Caputa et al (2013), Dickson (2000), Housman et al (2006), Issa et al (2001), Liu et al (2009Liu et al ( , 2012, Stewart et al (2011aStewart et al ( , b, c, 2012, Strauss et al (2012), Su et al (2011 b), Wu et al (2009), Zhao et al (2010, and Zielke et al (2002) The high variability in ARA rates reported in the literature may at least partly reflect methodological limitations of the assay. ARA is based on the fact that the enzyme nitrogenase, which is normally responsible for catalyzing the reduction of N 2 to NH 3 , can also reduce acetylene to ethylene, the latter reaction being an indirect measure of nitrogenase activity.…”
Section: Studies Measuring Nitrogen Fixation Using the Ara Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…14.3). Barger (2003), Barger et al (2013), Belnap (2002a, b), Billings et al (2003), Caputa et al (2013), Dickson (2000), Housman et al (2006), Issa et al (2001), Liu et al (2009Liu et al ( , 2012, Stewart et al (2011aStewart et al ( , b, c, 2012, Strauss et al (2012), Su et al (2011 b), Wu et al (2009), Zhao et al (2010, and Zielke et al (2002) The high variability in ARA rates reported in the literature may at least partly reflect methodological limitations of the assay. ARA is based on the fact that the enzyme nitrogenase, which is normally responsible for catalyzing the reduction of N 2 to NH 3 , can also reduce acetylene to ethylene, the latter reaction being an indirect measure of nitrogenase activity.…”
Section: Studies Measuring Nitrogen Fixation Using the Ara Methodsmentioning
confidence: 99%
“…In a series of early experiments, Hardy et al (1968) confirmed that this theoretical ratio ranged between 3 and 4 for bacterial cultures and legumes under laboratory and field conditions. Since this time, however, actual results from field and laboratory studies of biocrusts report that conversion ratios can range from 0.022 to 3.49 (Liengen 1999a;Stewart et al 2011a;Caputa et al 2013). Deviation (usually downwards) from the 3-4:1 ratio can result from several factors and may include the following:…”
Section: Studies Measuring Nitrogen Fixation Using the Ara Methodsmentioning
confidence: 99%
See 3 more Smart Citations